PROBLEM OF GENERIC REPLACEMENT: ADVANTAGES AND DISADVANTAGES - S. N. Tolpygina; S. Yu. Martsevich (Столичная издательская компания, 2016)
The main differences between original and generic drugs as well as registration criteria for generics are described. Possible reasons of discrepancy in bioequivalence and therapeutic equivalence of original and generic drugs are reviewed. The examples of such a discrepancy as a result of comparative clinical trails (enalapril maleate) are discussed. Approaches to planning of comparative trails on drug therapeutic equivalence are presented.